Саноат чиқиндиларининг энтомофаунага техноген таъсирини экологик баҳолашнинг умумий таҳлили (SCIENCE and SOCIETY, 2023)
The article presents a general analysis of the ecological assessment of the effects of unpleasant anthropogenic factors on entomofauna in the biosphere. The results of environmental monitoring are presented on measures to reduce or eliminate such man- made loads, to limit the negative impact on the ecosystem before critical irreversible situations occur.